Comparison of ziprasidone and olanzapine on cognitive function in patients with schizophrenia at different stages: a prospective study in Huai’an, China - Yao, Jingjing; Liu, Zeliang; Xiao, Xiaoming; Zhang, Liu; Qi, Shouhui; Ge, Yangcheng; Han, Hua; Wang, Xiuling (Frontiers in Behavioral Neuroscience, 2025)
ObjectiveTo compare the effects of ziprasidone and olanzapine on cognitive function in patients with first-episode schizophrenia and chronic schizophrenia at different stages.MethodsCognitive function tests were performed on chronic schizophrenic patients who took olanzapine for a long time, first-episode drug-free schizophrenic patients, and healthy controls.ResultsThere were significant differences in the digit span test, Stroop color and word test, auditory verbal learning test N2, N3, N4, trail-making test, verbal fluency test, and clock drawing test between first-episode drug-free schizophrenic patients and healthy controls (p < 0.05). Compared with patients with chronic schizophrenia, there were significant differences in the digit span test, Stroop color and word test B, auditory verbal learning test, trail making test B, and clock drawing test in patients with first-episode schizophrenia after 4 weeks of olanzapine treatment (p < 0.05). Compared with patients with chronic schizophrenia after 4 weeks of Ziprasidone treatment, patients with first-episode schizophrenia had significant differences in the digit span test, Stroop color, and word test, auditory verbal learning test N3, and clock drawing test after 4 weeks of olanzapine treatment (p < 0.05). Compared with patients with chronic schizophrenia who were treated with Ziprasidone for 12 weeks, there were significant differences in Stroop color and word test A, auditory verbal learning test N3, and clock drawing test in patients with first-episode schizophrenia after 4 weeks of olanzapine treatment (p < 0.05).ConclusionPatients with schizophrenia have cognitive dysfunction in the early stage of onset. The combination of ziprasidone and olanzapine can effectively improve cognitive dysfunction and promote the recovery of social functions of patients.